Pemodelan Sistem Dinamik Ketercapaian Kontribusi Biodiesel dalam Bauran Energi Indonesia 2025 - Handoko, Hamdan; Sa'id, Endang Gumbira; Syaukat, Yusman; Purwanto, Widodo W (Jurnal Manajemen Teknologi, 2012)
AbstractBiodiesel industry in Indonesia commercially emerged in 2005 driven by concerns on energy security triggered by high oil price, increasing environmental demand to reduce CO2 emission, while leveraging on Crude Palm Oil feed stock availability. The Government of Indonesia mandated biodiesel to contribute 10.22 million kilo litre in 2025 energy mix target, beside current weak industry performance of 27% low utilization ratio of biodiesel plant installed capacity of 4.2 million ton per annum. A system dynamic model, called Indonesia Biodiesel Industry Dynamic Model, has been developed as a platform to study the structure and behaviour of the biodiesel industry enriched with inputs from biodiesel related experts panel discussion and interview and to simulate the impact of energy policy interventions, such as biodiesel subsidy, diesel subsidy reduction and removal, blending mandate, and diesel environmental tax to the performance of biodiesel production, industry profitability EBITDA and Carbon Emission Reduction (CER) during simulation period of 2005-2030. Based on the scenario 1 of MDIBI, targeted 10.22 million tones per annum contribution of biodiesel in 2025 Indonesia's energy mix would not be achieved with current structure and condition, mainly due to three factors, which are  (i) low mixture of biodiesel-diesel mandate, (ii) a relatively limited supply of CPO raw materials which must be allocated for competing demand from cooking oil, oleofoods, oleochemicals and biodiesel industries, and (iii) currently available limited public service obligation (PSO) market.Keywords: biodiesel industry, system dynamic modelling, energy policy, energy mix, Indonesian                biodiesel.